Bhjet: a public multizone, steady state jet + thermal corona spectral model. Issue 4 (11th October 2022) - Lucchini, M; Ceccobello, C; Markoff, S; Kini, Y; Chhotray, A; Connors, R M T; Crumley, P; Falcke, H; Kantzas, D; Maitra, D
ABSTRACT: Accreting black holes are sources of major interest in astronomy, particular those launching jets because of their ability to accelerate particles, and dramatically affect their surrounding environment up to very large distances. The spatial, energy, and time-scales at which a central active black hole radiates and impacts its environment depend on its mass. The implied scale-invariance of accretion/ejection physics between black hole systems of different central masses has been confirmed by several studies. Therefore, designing a self-consistent theoretical model that can describe such systems, regardless of their mass, is of crucial importance to tackle a variety of astrophysical sources. We present here a new and significantly improved version of a scale invariant, steady-state, multizone jet model, which we rename BHJet, resulting from the efforts of our group to advance the modelling of black hole systems. We summarize the model assumptions and basic equations, how they have evolved over time, and the additional features that we have recently introduced. These include additional input electron populations, the extension to cyclotron emission in near-relativistic regime, an improved multiple inverse-Compton scattering method, external photon seed fields typical of active galactic nucleus, and a magnetically dominated jet dynamical model as opposed to the pressure-driven jet configuration present in older versions. In this paper, we publicly release the code on GitHub and, in order to facilitate the user's approach to its many possibilities, showcase a few applications as a tutorial.